Factorial Structure Determining The Intention To Vote Ecology - Cruz García Lirios (Malikussaleh Social and Political Reviews, 2022)
The political system in which it is possible to observe the similarities and differences between groups for and against presidential candidates based on processes of negotiation, mediation, conciliation and arbitration around the management and administration of Information Technologies and Communication is known as governance. This is a growing phenomenon as local or federal elections approach and digital networks are exacerbated as instruments for the promotion or dissuasion of a candidate. In this sense, the objective of the study was to optimize the Governance instrument of the Cyber Political Culture of Carreón (2016) in order to pay the reliability and validity of it; explore the relationship between preferences and expectations regarding voting intentions in a non-probabilistic sample of students using digital networks. From a structural model it was found that the consensus expectation factor determined the intentions to vote. The scope and limits of the exploratory factor analysis of main axes with a simple and oblique promax rotation regarding the confirmation of an orthogonal structure are discussed